2010
DOI: 10.1017/s1461145709991155
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence variants of the FKBP5 gene are associated with unipolar depression

Abstract: FKBP5 is a glucocorticoid receptor-regulating co-chaperone of hsp-90 and, therefore, is suggested to play a role in the regulation of the hypothalamic-pituitary-adrenocortical system and the pathophysiology of depression. Previously, three studies identified single nucleotide polymorphisms (SNPs) in the FKBP5 gene associated with response to antidepressants, and one study found an association with diagnosis of depression. We selected five markers from the region of interest. A case-control sample comprising 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 26 publications
4
90
2
Order By: Relevance
“…Similarly, elevated glucocorticoid levels have been associated with larger amygdala volumes (Buss et al 2012;Lupien et al 2011). Considering a heightened amygdala response and a larger volume as possible endophenotypes for stress-related disorders, the present findings are in line with previous reports suggesting an important role of the FKBP5 T allele in mood disorders (Appel et al 2011;Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and PTSD (Binder et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, elevated glucocorticoid levels have been associated with larger amygdala volumes (Buss et al 2012;Lupien et al 2011). Considering a heightened amygdala response and a larger volume as possible endophenotypes for stress-related disorders, the present findings are in line with previous reports suggesting an important role of the FKBP5 T allele in mood disorders (Appel et al 2011;Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and PTSD (Binder et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, T homozygotes were found to exhibit elevated cortisol levels during recovery after stress (Ising et al 2008). In line with this, rs1360780 has been associated with psychopathology such as mood disorders (Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and suicidality (Brent et al 2010). Moreover, this SNP has been shown to interact with childhood abuse in predicting PTSD symptoms (Binder et al 2008) and susceptibility to depression (Appel et al 2011), with an increased risk in the TT genotype following childhood abuse.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The identified candidate genes associated with cortisol concentrations may enhance discovery of genes associated with immune, metabolic, and behavioral traits in humans. Similar studies have identified candidate genes associated with cortisol concentrations that are also causally associated with depression (Gottesman and Gould 2003;Zobel et al 2010;Velders et al 2011).…”
Section: Discussionmentioning
confidence: 66%
“…The rs1360780 T allele was identified as the risk allele by three studies, the rs9470080 T allele by two studies, and the rs3800373 C allele by one study (Zannas and Binder 2014). Some studies did not take into account FKBP5 environment interactions and three studies found that the rs1360780 T allele was associated with increased risk of depression (Lekman et al 2008;Lavebratt et al 2010;Szczepankiewicz et al 2014), two studies found an effect of rs4713916 (Zobel et al 2010;Szczepankiewicz et al 2014), and non-replicated findings were reported for rs9470080, rs9296158 (Szczepankiewicz et al 2014) and rs3800373 (Zobel et al 2010).…”
Section: Genetic Polymorphismsmentioning
confidence: 99%